THE EFFECT OF ADMINISTERING (Moringa oleifera L.) LEAF EXTRACT IN DRINKING WATER ON BROILER PERFORMANCE - I M. F. S., Saputra; Siti, N. W.; Candrawati, D. P. M. A. (Jurnal Peternakan Tropika, 2024)
Broilers are poultry that have high productivity such as very fast growth and efficiency in utilizing feed so that the production price is relatively affordable, in addition to having superior broilers have the disadvantage of being susceptible to disease, therefore it is necessary to add feed additives such as AGP ( Antibiotic Growth Promoters), however, in the long run, the use of AGP can cause resistance and create residues that are harmful to consumers. An alternative that can be used as a substitute for AGP is Moringa leaf extract. This study aims to determine the effect of giving Moringa leaf water extract in drinking water on broiler performance. This research was conducted in Banjar Dinas Tiyinggading, Tiyinggading Village, West Selemadeg District, Tabanan Regency, Bali. The study starts from July 15, 2023, to August 20, 2023. The design used was a complete randomized design (RAL) consisting of four treatments and four repeats. Each test used four broilers with an average body weight of 41.55g±2.41, so the total broilers used were 64. The treatment given is (P0) broiler chickens without moringa leaf extract, (P1) 2% moringa leaf extract, (P2) 4% moringa leaf extract, and (P3) 6% moringa leaf extract. The variables observed were ration consumption, drinking water consumption, initial and final body weight, weight gain, and feed conversion ratio . The results showed that the administration of Moringa leaf extract in drinking water at the level of 2-6% had no real effect (P>0.05) on ration consumption, drinking water consumption, weight gain, and feed conversion ratio. From this study, it can be concluded that giving Moringa leaf extract at the level of 2-6% in drinking water has not been able to improve broiler performance.